Celeste M. Nyaga - Karwe village, Makengi - Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
The new seeds varieties and education on different farming techniques are helping Kenyan farmers adapt to challenges posed by changing rain patterns.